2014
DOI: 10.1002/cplu.201402187
|View full text |Cite
|
Sign up to set email alerts
|

The Major Influences of Substituent Size and Position of 3,4‐Propylenedioxythiophene on the Formation of Highly Hydrophobic Nanofibers

Abstract: The influence of the substituent size and position of 3,4‐propylenedioxythiophene (ProDOT) on the surface properties of the corresponding electrodeposited polymer films is shown. The study investigates the influence on the formation of hydrophobic nanofibers using two substituents (isopropyl and tert‐butyl). The 3‐position of ProDOT is the best for the formation of nanofibers, because it leads to the longest polymer chains while also leading to the highest intrinsic hydrophobicity, two effects that increase th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…Indeed, it was demonstrated that the main factor influencing the surface morphology is the solubility of the oligomers formed in the first instances of the polymerization. [52,53] Here, the solubility is affected by the substituent hydrophobicity/polarity and the polymer chain lengths, which are differentfor the two polymers.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, it was demonstrated that the main factor influencing the surface morphology is the solubility of the oligomers formed in the first instances of the polymerization. [52,53] Here, the solubility is affected by the substituent hydrophobicity/polarity and the polymer chain lengths, which are differentfor the two polymers.…”
Section: Resultsmentioning
confidence: 99%
“…14,15 This change explains the increase in both the surface hydrophobicity and oleophobicity as the fluorinated chain length decreases. The surface morphology (porous and fibrillar network) is the same whatever the fluorinated chain length is and is also the same than the morphology of the starting polymer PEDOT-N 3 .…”
Section: Surface Morphologymentioning
confidence: 98%
“…9,10 Usually, fluorinated materials are used for their high intrinsic oleophobicity while the wetting of oils can be impeded by controlling the geometrical parameters of the surface structures. Due to the possibility to control the surface morphology by several parameters such as electrochemical parameters or the monomer structure, 14,15 the electrodeposition of conducting polymers is a fascinating technique for superhydrophobic or superoleophobic properties. [11][12][13] Anyway the surface morphology is definitely a key point and need to be controlled.…”
Section: Introductionmentioning
confidence: 99%
“…The ProDOT heterocycle is one of the best monomers for its polymerization ability but also for the formation of nanostructures such as nanofibers [28,29]. Specifically, the substitution in the 3-position was found to be the best for the formation of nanostructures because it leads to the highest polymer chains [34].…”
Section: Introductionmentioning
confidence: 99%